Синтез кислородсодержащих гетероциклических бананоподобных соединений - Новикова, Н.С.; Кондратьева, Р.В.; Максименко, С.И.; Ковальчук, Б.А. (Видавничий дім "Академперіодика" НАН України, 2007)
For the first time, the banana-shaped compounds 1,3-benzenedicarbonic acid diesters containing 1,3-dioxanic cycle have been synthesized. Analogs to these compounds, but on the basis of 3-hydroxybenzoic acid, have not been prepared. The separated final reaction products according to NMR1H measurements are 4(5-nonyl-[1,3]-dioxane-2-yl)phenyl esters of 3-bromine-4(4-alkyloxybenzoyloxy)benzoic acids. These compounds possess the mesomorphic properties.